Implementasi Peraturan Daerah Kabupaten Pasaman Nomor 3 Tahun 2017 tentang Pendidikan Gratis Perspektif Siyasah Tanfiziyah (Studi Kasus di Nagari Lansek Kadok) - Bunga Vajar Lestari; Sofia Ridha (AHKAM, 2026)
The free education policy is an important instrument in ensuring access to education for society; however, its implementation still faces challenges at the local level, as reflected in the continued presence of junior secondary school-age children who have dropped out of school in Nagari Lansek Kadok. This study aims to analyze the implementation of Pasaman Regency Regional Regulation Number 3 of 2017 concerning Free Education, identify the factors inhibiting its implementation, and examine the policy from the perspective of Siyasah Tanfiziyah. This study used a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that the free education policy at the junior secondary school level in Nagari Lansek Kadok has been implemented, but it has not yet run optimally because some students still drop out of school. The main obstacles to the implementation of this policy include low public awareness of the importance of education, insufficient policy socialization, geographical conditions, limited educational support facilities, and the suboptimal role of the nagari government and coordination among stakeholders. From the perspective of Siyasah Tanfiziyah, the implementation of the free education policy has not fully reflected the principles of public benefit, justice, and government responsibility in fulfilling and guaranteeing the community’s right to education. The conclusion of this study emphasizes that the effectiveness of the free education policy requires strengthened socialization, an enhanced role of the nagari government, and more optimal coordination among implementing actors so that the goal of fulfilling the community’s right to education can be achieved more equitably.